The Long Pentraxin PTX3 as a Humoral Innate Immunity Functional Player and Biomarker of Infections and Sepsis - Porte, Rémi; Davoudian, Sadaf; Asgari, Fatemeh; Parente, Raffaella; Mantovani, Alberto; Garlanda, Cecilia; Bottazzi, Barbara (Frontiers in Immunology, 2019)
The first line of defence in innate immunity is provided by cellular and humoral mediators. Pentraxins are a superfamily of phylogenetically conserved humoral mediators of innate immunity. PTX3, the first long pentraxin identified, is a soluble pattern recognition molecule rapidly produced by several cell types in response to primary pro-inflammatory signals and microbial recognition. PTX3 acts as an important mediator of innate immunity against pathogens of fungal, bacterial and viral origin, and as a regulator of inflammation, by modulating complement activation and cell extravasation, and facilitating pathogen recognition by myeloid cells. In sepsis, PTX3 plasma levels are associated with severity of the condition, patient survival, and response to therapy. In combination with other established biomarkers, PTX3 could improve stratification of sepsis patients and thus, complement the system of classification and monitoring of this disease.